(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
Toxic effects of Cu2+, Zn2+ and Cd2+ in tomato plants were the reduction in vegetative growth of seedlings and also in flowering and fruiting. Toxicity of these heavy metals resulted in a reduction in chlorophyll a, chlorophyll b and soluble sugars, but in an increase in proline. Toxic metal stress caused a 71.71, 77.70 and 11.90% increase in the activities of peroxidase, catalase and ascorbic acid oxidase, respectively. With respect to the total uptake of Cd2+, the biggest sink for the metal was provided by roots with 72.80% retention followed by 22% in the stem. Accumulation of Cd2+ and Zn2+ gradually increased in the order of root, stem and leaves, but for Cu2+ that was reversed, that is, it increased in the order of leaf, stem and root. A new consideration of metals bioavailability is discussed in terms of their respective solubility product constants, pH of precipitation, and metal complexation. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.9754 Bangladesh J. Sci. Ind. Res. 48(4), 229-236, 2013